Training Approaches for Improving School Managers’ Conflict Resolution Skills: A Case Study - Nyet, Moi Siew; Scott Jones (SCIENTIA EDUCOLOGICA, 2018)
This research took a case study approach to researching the common conflicts faced by school managers, their sources, impacts and the approaches used to manage them. The research involved 18 in-service Malaysian school managers who undertook a 16-hour professional development workshop where they engaged with different conflict management tools. Data on participants’ workplace experience in resolving conflicts were captured through written diaries collected before and two months after the workshop, and face-to-face semi-structured interviews during the following months. Intragroup conflicts due to goal incompatibility were the most common conflicts faced. Negative impacts of conflicts on school communities far outweighed the benefits. Participants reported that the most effective approaches to resolving workplace conflicts were sincere efforts in problem-solving coupled with (1) culturally relevant negotiations and coaching (e.g. using a GROW coaching model); (2) stakeholder and conflict analysis, to consider and respond to everyone’s needs and feelings; and (3) reflecting on personal conflict management styles and adopting a positive attitude to personal and professional development. Certain elements in customary approaches such as respectful discussion and consultation were found relevant in resolving several of the participants’ workplace conflicts. It is suggested that practical training courses on conflict management that build on people’s strengths should be included in the curricula of further and higher education institutions and teacher training institutes.